Early Childhood Educator perspectives on the first year of implementing an Outdoor Learning Environment in Singapore. (3rd July 2017) - Lyne Strachan, Andrea; Lim, Elaine; Yip, Hoe Yin; Lum, Grace
ABSTRACT: Using a qualitative case-study approach, this small-scale pilot study explores the potential challenges and opportunities faced by early childhood educators in their first year of implementing a dedicated Outdoor Learning Environment (OLE) at their school. Participants include two Kindergarten teachers working at a large international school in Singapore. Key findings reveal the ways in which students and teachers act as co-designers of learning in OLEs, and the ways in which OLEs can provide a unique learning context for supporting learner curiosity and developing resilience in children. The role that collaboration plays amongst teachers, students, and families, in co-designing learning engagements and mitigating challenges associated with implementing an OLE, is explored. Knowledge and insights gained through conventional content analysis, and links to the ways in which OLEs have the potential to facilitate the development of twenty-first century competencies in young children, is discussed.